THE OPTIMAL EXTRACTION PARAMETERS AND ANTI-DIABETIC ACTIVITY OF FLAVONOIDS FROM IPOMOEA BATATAS LEAF - Li, F.; Li, Q.; Gao, D.; Peng, Y. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Extraction parameters of flavonoids from Ipomoea batatas leaf (FIBL) and anti-diabetic activity of FIBL on alloxan induced diabetic mice were studied. The optimal extraction parameters of FIBL were obtained by single factor test and orthogonal test, as follows: ethanol concentration 60 %, ratio of solvent to raw material 30 , extraction temperature 75 ℃ and extraction time 1.5 h , while extraction yield of FIBL was 5.94 %. FIBL treatment (50, 100, and 150 mg/ kg body weight) for 28 days resulted in a significant decrease in the concentration of fasting blood glucose (FBG), total cholesterol (TC) and triglyceride (TG) in diabetes mellitus mice. Furthermore, FIBL significantly increased body weight (bw) and serum high-density lipoprotein cholesterol (HDL-c) level. The data demonstrated FIBL at the dose of 100 mg/kg bw exhibited the optimal effect. The above results suggest that FIBL can control blood glucose and modulate the metabolism of blood lipid in diabetes mellitus mice.